2019
DOI: 10.14200/jrm.2019.0107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Anti-Inflammatory Diet in People with Diabetes and Pre-Diabetes: A Randomized Controlled Feeding Study

Abstract: Introduction: Inflammation underlies a variety of chronic medical conditions, including diabetes. The anti-inflammatory diet, one that excludes foods that may stimulate inflammation and includes foods that reduce inflammation, may improve inflammatory biomarkers in people with diabetes and pre-diabetes. Study Design: Thirty participants with diabetes or pre-diabetes were randomized (2:1) in a controlled feeding study that compared the anti-inflammatory diet (n=20) to a control diet (n=10) based on the Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…However, we can infer this indirectly since the intensity of inflammatory infiltration in tissues has been evaluated in none of these studies. What is also worth mentioning, the benefits in the inflammatory status could be contributed to the weight loss rather than the specific elimination of pro-inflammatory compounds and/or inclusion of compounds with anti-inflammatory properties shown in vitro [88]. Moreover, most clinical studies on the influence of the dietary intervention on the course of metaflammation have several limitations that include: (i) small sample sizes, limiting the power of the intervention to detect an effect; (ii) lack of a transparent definition of the dietary intervention, rendering it difficult to evaluate the role of a particular dietary modification on the inflammatory status; (iii) difficulties in assessing compliance with dietary recommendations.…”
Section: Diet and Natural Compoundsmentioning
confidence: 99%
“…However, we can infer this indirectly since the intensity of inflammatory infiltration in tissues has been evaluated in none of these studies. What is also worth mentioning, the benefits in the inflammatory status could be contributed to the weight loss rather than the specific elimination of pro-inflammatory compounds and/or inclusion of compounds with anti-inflammatory properties shown in vitro [88]. Moreover, most clinical studies on the influence of the dietary intervention on the course of metaflammation have several limitations that include: (i) small sample sizes, limiting the power of the intervention to detect an effect; (ii) lack of a transparent definition of the dietary intervention, rendering it difficult to evaluate the role of a particular dietary modification on the inflammatory status; (iii) difficulties in assessing compliance with dietary recommendations.…”
Section: Diet and Natural Compoundsmentioning
confidence: 99%
“…Our literature search found 842 references from a systematic search of electronic databases, of which 47 full-text-available studies were retrieved and screened for eligibility as part of the selection process ( Figure 1 ). After reviewing the full texts of 19 articles, nine were eliminated because they did not meet the inclusion criteria; one study was duplicate study population [ 23 ]; two studies had ineligible study design, and they were excluded because they reported the outcome for adherence to the Mediterranean diet (MD) as a binary variable (adherence or not adherence) without quantitative biomarkers [ 24 , 25 ]; two studies were part of a macro-project, and we used the eligible study version with the longest duration period [ 26 , 27 ]; one study compared lifestyle interventions with the use of insulin as medication [ 28 ]; one study showed incomplete monitoring assessment (no final values were presented, only basal values) [ 29 ]; one was a pilot study [ 30 ]; another was excluded due to a lack of data about biomarkers which we could not obtain even after contacting the authors (only mentioned their evaluation but did not report it) [ 31 ]. Finally, a total of 10 clinical trials [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ] met the inclusion criteria and were included in our systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this research are largely comparable with the numerous works of scientists dedicated to the therapeutic and prophylactic effect of dietary fiber on the body in various diseases. In particular, the work by Zwiki H. et al 2019 [19] points to the positive effect of dietary fiber in some forms of diabetes [15][16][17][18][19]. For many years, studies confirming the therapeutic effect of dietary fiber in obesity including in children and pregnant women, as well as diseases of the cardiovascular system, oncological and some others have been carried out [20][21].…”
Section: Discussionmentioning
confidence: 99%